Factor shares and the rise in corporate net lending - Jan Behringer (ZBW - Leibniz Information Centre for Economics, 2020)
The corporate sector has turned from a net borrowing position to a net lending position in many advanced countries over the past decades. This phenomenon is rather unusual as the corporate sector had historically borrowed funds from other sectors in the economy. In this paper, we analyze how changes in the distribution of income between wages and profits have affected corporate net lending in a sample of 40 countries for the period 1990-2016. A consistent finding is that an increase (decrease) in the corporate profit share leads to an increase (decrease) in corporate net lending, controlling for other corporate net lending determinants. We disentangle the effects of the profit share on corporate saving and investment and explore a number of alternative explanations of our results, including changes in the cost of capital, shifts in the composition of industrial sectors, the growing importance of intangible capital, and a temporary crisis phenomenon. We conclude that factor shares are an important driver of macroeconomic trends and that the rise in corporate profits has contributed considerably to the improvement in the corporate net lending position across countries.
Keywords: E21; E22; E25; G30; 330; Corporate saving; investment; income distribution; cost of capital